Alzheimer’s disease: a mini-review for the clinician - Madnani, Rishi S. (Frontiers in Neurology, 2023)
Alzheimer’s Disease (AD), the most common form of dementia, is a striking example of the connection between neurophysiological abnormalities and higher-order cognitive deficiencies. Since its initial description in 1906, research into the pathophysiology and etiology of AD has led to the illumination of an incredibly complex set of genetic and molecular mechanisms for the disease’s progression, characterized by much more than the neuropathological hallmarks of beta-amyloid (Aβ) plaques and neurofibrillary tangles (NFTs). In this mini-review, findings relating the neurodegeneration present in AD to its clinical presentation and treatment are summarized, with an emphasis on the interconnectedness of disease pathophysiology.